Chicken Egg White—Advancing from Food to Skin Health Therapy: Optimization of Hydrolysis Condition and Identification of Tyrosinase Inhibitor Peptides - Yap, Pei-Gee (Foods, 2020)
Active fragments (bioactive peptides) from the chicken egg white proteins were expected to exert tyrosinase inhibitory activities in which skin hyperpigmentation could be prevented. Egg white was hydrolyzed by trypsin, chymotrypsin and the combination of both enzymes. The enzyme treatments achieved >50% degree of hydrolysis (DH) at substrate-to-enzyme (S/E) ratio of 10–30 (w/w) and hydrolysis time of 2–5 h. A crossed D-optimal experimental design was then used to determine the optimal enzyme composition, S/E ratio and hydrolysis time in order to yield hydrolysates with strong monophenolase and diphenolase inhibitory activities. The optimized conditions 55% trypsin, 45% chymotrypsin, S/E 10:1 w/w and 2 h achieved 45.9% monophenolase activity inhibition whereas 100% trypsin, S/E 22.13:1 w/w and 3.18 h achieved 48.1% diphenolase activity inhibition. LC/MS and MS/MS analyses identified the peptide sequences and the subsequent screening had identified 7 peptides (ILELPFASGDLLML, GYSLGNWVCAAK, YFGYTGALRCLV, HIATNAVLFFGR, FMMFESQNKDLLFK, SGALHCLK and YFGYTGALR) as the potential inhibitor peptides. These peptides were able to bind to H85, H94, H259, H263, and H296 (hotspots for active residues) as well as F92, M280 and F292 (stabilizing residues) of tyrosinase based on structure-activity relationship analysis. These findings demonstrated the potential of egg white-derived bioactive peptides as skin health therapy.